How computers work the evolution of technology - White, Ron 1944- (Que, 2015)
This full-color, fully illustrated guide to the world of technology assumes nothing and explains everything. In addition to all the content you've come to expect from prior editions, this newly revised edition includes all new coverage of topics such as: how smartphones and tablet PCs put the power of a desktop computer in your hands-literally; how advances such as Facebook, Twitter, Google, eBay, and smartphones are expanding our universe of friends, knowledge, and opportunity; how increased miniaturization leads to new products, such as smartphone, smartwatches, and Google Glass; and, how computing technology takes advantages of quantum physics and innovations no one even imagined a few years ago.